Analysis of Teacher Professional Development at SDN Caturtunggal 4 Yogyakarta - Niendy; Fakhriya Nusaima; Yuliana Aisya; Muhammad Syukron; Wiji Hidayati (Education Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the implementation of the teacher professional  development program at SDN Caturtunggal 4 Yogyakarta in order to improve the competence and quality of learning. The research used descriptive qualitative methods with data collection techniques through in-depth interviews, direct observation, and documentation studies. The results show that professional development is carried out through various forms of training, such as Teacher Working Group (KKG) activities, webinars, Teacher Professional Education Program (PPG), and internal school training called "Senin Berbagi". This program provides a space to systematically share good practices between teachers. In addition, teachers' needs in mastering educational technology, understanding the latest curriculum and improving social skills were found. Although the program has a positive impact on teaching quality, challenges such as time constraints and low motivation remain. As a solution, the school replicates the training results by teachers who have participated in external training. The findings emphasize the importance of sustainable and collaborative professional development policies to deal with the dynamics of education in the digital era.